The wastewater quality from several industrial production branches and traditional production villages in the Day-Nhue river basin, North Vietnam - Anh, Nghiem Xuan; Quynh, Le Thi Phuong; Hieu, Vu Huu; Minh, Luu Thi Nguyet; Thuy, Duong Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 1, 2010)
Abstract. The Day-Nhue river system, which locates in the important economic region of the northern plains, covers a natural surface of 7949 km². The pollution of the Day-Nhue river system was mainly due to receiving untreated/ ineffective untreated wastewater discharges from the different sources in the basin. This paper focused on the industrial wastewater sources. Our purposes are to  i) collect information about the number and sizes of industrial production factories and traditional production villages; ii) establish the database of wastewater quality released from six main industrial production branches in the basin. The results obtained from our investigation during 1/2007–12/2009 showed that the total wastewater discharge from industrial production factories and traditional production villages reached to 100,000 m 3 /day and 45,000-60,000 m 3 /day, respectively. The wastewater quality of some industrial production branches exceeded the National technical regulation on industrial wastewater QCVN 24:2009/BTNMT. Most traditional production villages caused serious organic pollution. Keywords :  wastewater quality, industrial production, traditional production villages, Day- Nhue River.